Hubungan Indeks Massa Tubuh Dengan Kecepatan Berlari Pada Pemain Futsal Klub Ptks Medan 2021 - Bontor Labora Romauli Sibuea; Wahyu Wijanarko; Ida Aryani Pasaribu (Jurnal Kesehatan dan Fisioterapi, 2022)
Futsal is a football game with a smaller version, where players try to score goals against each other's group. Futsal players have a physical component that really determines the players can play with good performance or not. Among the components of body mass index (BMI) and running speed. Objective : To find out how BMI with running speed meters in PTKS Club futsal players in Medan in 2021. Methods : This study is a correlation study with a survey approach. The study will be carried out with 2 measurements: the first measurement will be carried out on BMI and the second measurement will be carried out on running speed. Results : this study obtained a p-value (0.626) where there is no significant relationship, this is because: the BMI characteristic data in this study showed no significant difference so that BMI did not have an impact on decreasing running speed in PTKS Club futsal players in Indonesia. Medan in 2021. Conclusion : There is no relationship between body mass index (BMI) and running speed meters in PTKS Club futsal players in Medan 2021.Keywords: Body mass index, Running speed